Tasawuf Humanistik Imam Al-Habsyi: Sebuah Kajian Hermeneutika Hans-Geog Gadamer - Muhamad Faisal Amiruddin; Syamsul Arifin; Helmi Syaifuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This paper examines “The Humanistic Sufism of Al-Imam Al-Habsyi through the Hermeneutical Perspective of Hans-Georg Gadamer.” It explores how the Sufi teachings of Al-Imam Al-Habsyi embody humanistic values that can offer enlightenment and guidance for contemporary life. Through Gadamer’s hermeneutical lens, this study seeks to create a dialogue between traditional Sufi teachings and the ever-changing needs of modern humanity. The humanistic Sufism formulated by Al-Imam Al-Habsyi emphasizes a balance between personal spiritual depth and social concern. Thus, moral cultivation not only strengthens one’s relationship with God but also fosters meaningful connections with fellow human beings. The research employs a descriptive-analytical qualitative approach by examining the works, sermons, and teachings of Al-Imam Al-Habsyi. Gadamer’s hermeneutical perspective—highlighting the importance of historical experience, pre-understanding, and the fusion of horizons—serves as a bridge to reinterpret the values of Sufism so they remain alive and meaningful in today’s context. The findings reveal that Al-Imam Al-Habsyi’s humanistic Sufism is grounded in five core values: (1) love for the Prophet as the source of moral and humanistic inspiration; (2) justice spanning spiritual, social, and economic dimensions; (3) the safeguarding of human dignity as a sign of sincere spirituality; (4) social solidarity as a tangible expression of compassion and empathy; and (5) social responsibility that guides individuals to contribute goodness in their daily lives. Through a hermeneutical approach, these values can be applied across various modern settings—ranging from education and leadership to social activities and interpersonal relations. This study concludes that Al-Imam Al-Habsyi’s humanistic Sufism represents a harmonious integration of spirituality, ethics, and social engagement. With the support of Gadamer’s hermeneutics, these teachings can be revitalized into practical and relevant guidelines for today’s society. When embodied in daily life, these values not only shape individuals of noble character but also help build a more just, peaceful, and compassionate society. The findings make an important contribution to the development of humanistic Sufism studies and offer practical guidance for those seeking to ground spiritual values in modern life. The study also opens pathways for further exploration of the implementation of humanistic Sufism in educational, social, and economic fields, as well as the use of other hermeneutical approaches to ensure that traditional teachings remain relevant amid contemporary challenges.